Glypican-4 trajectory predicts the risk of gestational diabetes mellitus and the requirement for insulin therapy during pregnancy - Tang, Lei; Li, Ping; Li, Ling (Frontiers in Endocrinology, 2025)
BackgroundGestational diabetes mellitus (GDM), characterized by the onset of glucose intolerance during pregnancy, results in a series of complications for maternal and fetal health. Oral glucose tolerance test (OGTT) for screening glucose metabolism is performed in mid-to-late pregnancy, which remains less time to optimize glycemic control. Glypican-4, an insulin-sensitive adipose hormone, exhibits correlations with metabolic indicators. This study aims to investigate the association between glypican-4 and the risk of developing GDM, as well as the effects on insulin therapy and postpartum glucose metabolism.MethodsBased on pregnancy 75-g OGTT results, 718 subjects were grouped into normal glucose tolerance (NGT, n = 345) and GDM (n = 373) groups. 373 GDM patients were divided into the diet (n = 237) and insulin (n = 136) groups according to the treatment of hyperglycemia in pregnancy. Based on postpartum 75-g OGTT results, 158 of the 373 GDM patients were further divided into the NGT after delivery (NGTd, n = 138) and abnormal glucose tolerance (AGT, n = 20) groups.ResultsGlypican-4 level was significantly higher in GDM than NGT subjects during pregnancy (P< 0.001). Glypican-4 was an independent predictor of GDM with the cut-offs were 0.40 ng/mL (5-12 weeks of gestation) and 0.79 ng/mL (13-23 weeks of gestation). Furthermore, glypican-4 level in the insulin group was higher than the diet group, which was a potential predictor of insulin therapy.ConclusionsGlypican-4 during pregnancy is associated with GDM risk, with higher levels indicating increased risk. Glypican-4 was also related to insulin therapy in GDM.